PENGARUH EKSTRUSI DAN PROTEKSI DENGAN TANIN PADA TEPUNG KEDELAI TERHADAP PRODUKSI GAS TOTAL DAN METAN SECARA IN VITRO - ganang sajati (Indonesian Journal of Food Technology, 2012)
The purpose of this study was to examine the influence of combined treatments of the extrusion process and the addition of a natural source of tannins (tea and or gambier wastes) of the total gas and methane production in soybean flour. The materials used in this study were soybean meal, tea waste, gambier, cow rumen fluid, alcohol, CO2, McDougall solution, 15% H2SO4, 0,5 N NaOH, 0,5 N HCl, 1% PP indicator and distilled water. The instruments used were analytical scales, test tubes, oven, extruder machine, waterbath, centrifuge, vacuum flaks, CO2 gas cylinder, 100ml syringes glass equipped with silicone hoses and clips to be closed and opened, vaccuntainer, erlenmeyergas chromatography, special flute tube and distillation flask, glass beaker, Erlenmeyer, incubator, pipettes, measuring instruments, magnetic stirrer, peristaltic pump to drain the rumen fluid and heater. This study used completely randomized design in 2x3 factorials and 3 replicates by a-factor (a0 = no extruided and a1= extruded) and b-factor(b0= no tannins, b1= tea waste tannins, b2= gambier tannin). The parameters observed including total gas and methane production, the data were taseted by usisng analysis of varience and followed by the Duncan test. The results indicate that there is no interaction between the extrusion and the addition of tannins to total gas production, while the production of methane gas does not indicate any influence (p < 0.05). It is concluded that the extrusion and protection with natural tannins of soybean flour have impacted on decreased in the production of total gas and methane production